A framework for understanding shared substrates of airway protection (Journal of Applied Oral Science, 2014)
Deficits of airway protection can have deleterious effects to health and quality of life. Effective airway protection requires a continuum of behaviors including swallowing and cough. Swallowing prevents material from entering the airway and coughing ejects endogenous material from the airway. There is significant overlap between the control mechanisms for swallowing and cough. In this review we will present the existing literature to support a novel framework for understanding shared substrates of airway protection. This framework was originally adapted from Eccles' model of cough28 (2009) by Hegland, et al.42 (2012). It will serve to provide a basis from which to develop future studies and test specific hypotheses that advance our field and ultimately improve outcomes for people with airway protective deficits.